What does the primary school student know about the map in 2013? - Hennerdal, Pontus (Stockholm University, 2019)
In 1968, Sonja Peterson conducted a study that included all students from grade 1 to grade 9 in Arvika, Sweden. That study was named: Vad vet grundskoleeleven om kartan? [What does the primary school student know about the map?] and was published in 1971 in the report series: Rapporter från Pedagogiska institutionen i Göteborg [Reports from the Department of Education in Gothenburg]. As a part of the doctoral studies Pontus Hennerdal conducted at Stockholm University, he recreated parts of the test Peterson used in her study. Together with some new questions, Hennerdals study was also carried out with students in Arvika during 2013. This time with students from grade 2 to year 9. This archive consists of answers from the 1206 completed questionnaires that were filled in during the spring term 2013 during Hennerdals Arvika study. Also the archive include some comparisons with the data Peterson collected 45 years earlier.

During the spring term of 2013, tests(see attached files) were distributed to all classes (grade 2 to 9) in Arvika, Sweden. All grades did not have all test sheets. The teachers conducted the test with each class based on the instruction:

The intention is that the questions should be self-instructing, that the only thing the students need in addition to the questions is a pen and an eraser, and that the answers to the questions should be received during an hour. But the study is not ruined by helping students to understand question they find unclear (explain the question, not the concept), let them use draft paper and their own ruler, or let someone draw a little over the time if the teacher finds it possible.

Under 1968 genomförde Sonja Peterson en studie som omfattade alla elever från årskurs 1 till årskurs 9 i Arvika. Den studien fick namnet: Vad vet grundskoleeleven om kartan? och publicerades 1971 i rapportserien: Rapporter från Pedagogiska institutionen i Göteborg. Som del av de doktorandstudier Pontus Hennerdal genomförde vid Stockholms universitet återskapades delar av det prov Peterson använt i sin studie. Tillsammans med några nya frågor genomfördes under 2013 även Hennerdals studie med elever i Arvika. Denna gång elever från årskurs 2 till årskurs 9. Detta arkiv består av de svar från de 1206 ifyllda enkäter som fylldes i under vårterminen 2013 under Hennerdals Arvikastudie med jämförelser med det material Peterson samlade in 45 år tidigare.

Under vårterminen 2013 distribuerades prov (se bifogade filer) till samtliga klasser (årskurs 2 till 9) i Arvika. Alla årskurser hade inte alla provblad. Lärarna genomförde provet med respektive klass utifrån instruktionen:

Avsikten är att frågorna ska vara självinstruerande, att det enda som eleverna behöver förutom frågorna är en penna och ett radergummi, samt att svarandet på frågorna skall hinnas med under en lektionstimme. Men studien förstörs inte av att man hjälper elever att förstå någon fråga de finner oklar (förklara frågan, inte konceptet frågan gäller), låt dem använda kladdpapper och egen linjal eller låter någon dra över lite på tiden om läraren finner det möjligt i relation till övrig undervisningstid.
Vad vet grundskoleeleven om kartan 2013?
Keywords: education; utbildning; Geography; Geografi; Maps as Topic; Kartor som ämne; Compulsory and pre-school education; Obligatorisk utbildning och förskoleutbildning; Social Sciences; Samhällsvetenskap; Educational Sciences; Utbildningsvetenskap; Didactics; Didaktik; Human Geography; Kulturgeografi; Other Educational Sciences; Annan utbildningsvetenskaplig forskning